Southern Pride as Reflected in Tennessee Williams’ The Glass Menagerie - Tini Mogea (Pusat Riset dan Inovasi Nasional, 2023)
This research is mainly intended to reveal the old southern pride reflected in the characteristics of Amanda, a southern lady. In conducting this research, the writer uses qualitative research, in which the data are collected in the form of words and the writer is the key instrument. The data were taken from the work itself and other relevant books supporting the data. In analyzing the data, the writer uses a mimetic approach, which considers that literary work is a reflection and imitation of aspects of the universe. The result of this research shows that in the southern part of America before the Civil War, there was a custom called